RELIABILITY PIPELINE TRANSPORT SYSTEMS AND MEANS OF INCREASE - and and (Municipal economy of cities. Series: «Economy science», 2013)
In this article the analysis of modern methods of the increase of reliability of functioning of pipeline systems is executed, traditional (parametrical and structural ones) methods and non traditional methods, methods of the increase of reliability of their functioning on foundation of denouement of separate levels are also considered.